Formal and informal gender wage gaps: the impact of trade liberalization in Brazil - Rocha, Pedro Henrique Cavalcanti (2020)
Trade liberalization is closely associated with competitive shocks which generate differentiated effects in the formal and informal sectors, especially in developing countries. We use the Brazilian trade liberalization episode in early 1990 as a natural experiment to test Becker’s theory on discrimination, but including the informal sector. In our model, heterogeneity on the firm’s productivity and discrimination explain the effects of trade liberalization on the gender wage gap in the formal and informal sector. The model establishes a causal link between trade reform, firm productivity change, and reallocation of discriminatory firms between sectors, which implicate in varied effects of trade liberalization on the average gender wage gap and discrimination. Overall results indicate that a reduction in 1 % in tariff decreases the gender wage gap between 3% to 8% in the formal sector and increases the gender wage gap between 5% to 8% in the informal sector.